High and Low in Music: Canons versus Charts - Bjurström, Erling (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2024)
The article explores the relationship between canonicity and the border between high and low culture within music. It departs from the assumption that the border is mainly constituted and upheld by what are considered oppositional high and low poles. Likewise, the border rests on musical as well as extramusical dimensions and can consequently be discerned in music as well as its social, cultural, and economic infrastructure or context. By becoming a crucial building block in the infrastructure of popular music in the 1940s, music charts laid the groundwork for a more clear-cut antagonism between high and low in music, based on the impetus of an implied opposition between canonicity and charts. Even though this opposition remains an indicator – and a microcosm – of the border between high and low in music, the cultural weight and status of both the classical canon and the pop charts have changed considerably, not least because of the so-called digital revolution. The last part of the article discusses how this shift from analog to digital has altered the relationship between canonicity and the distinction of high and low in music.